2018
DOI: 10.1002/jaba.530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulus presentation order during auditory–visual conditional discrimination training for children with autism spectrum disorder

Abstract: Children with autism spectrum disorder are typically taught conditional discriminations using a match-to-sample arrangement. Consideration should be given to the temporal order in which antecedent stimuli (the sample and comparison stimuli) are presented during match-to-sample trials, as various arrangements have been used in the extant literature. The purpose of the current study was to compare the effects of four stimulus presentation orders on the acquisition of auditory-visual conditional discriminations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 54 publications
3
31
0
Order By: Relevance
“…We conducted up to 15 sessions per day, in a random without replacement order, at least 10 min apart, and up to 5 days per week based on the experimenter and participant's availability. The experimenter presented the sample and comparison stimuli using a comparison‐first arrangement (Cubicciotti et al, ). The experimenter required the participant to touch the condition‐specific stimulus binder and tact the condition‐correlated color before each session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted up to 15 sessions per day, in a random without replacement order, at least 10 min apart, and up to 5 days per week based on the experimenter and participant's availability. The experimenter presented the sample and comparison stimuli using a comparison‐first arrangement (Cubicciotti et al, ). The experimenter required the participant to touch the condition‐specific stimulus binder and tact the condition‐correlated color before each session.…”
Section: Methodsmentioning
confidence: 99%
“…Early intensive behavioral intervention programs commonly target AVCDs (Cubicciotti, Vladescu, Reeve, Carroll, & Schnell, ; Schneider, Devine, Aguilar, & Petursdottir, ). This is not surprising considering many skills require individuals to differentially respond to the verbal behavior of others.…”
mentioning
confidence: 99%
“…Petursdottir and Aguilar (2016) found faster acquisition when they presented the sample stimulus prior to the comparison stimuli with learners who showed typical development. Other research has found the samplefirst procedure to be more effective for the majority of participants (Cubicciotti, Vladescu, Reeve, Carroll, & Schnell, 2018;Schneider, Devine, Aguilar, & Pettursdottir, 2018); however, the participants in each of these studies did not meet our criteria for novice learners relative to acquisition of auditory-visual conditional discriminations. Future research should compare a sample-first procedure with the comparison-first procedure with novice learners while holding other aspects of the treatment package constant.…”
Section: Discussionmentioning
confidence: 78%
“…The experimenter presented antecedent stimuli using a comparison‐first arrangement wherein she revealed the comparison array, waited 3 s, and then presented the sample stimulus (Cubiciotti, Vladescu, Reeve, Carrol, & Schnell, ). The participant had 5 s to respond.…”
Section: Methodsmentioning
confidence: 99%